BIOSAN Latrine for Refugee Camps - Makhanu, S. K.; Waswa, George (My University, 2010)
Provision for energy needs, safe water supply and sustenance of environmental quality are among the topmost challenges facing the present human society. Water and sanitation inadequacies also hinder economic and social development, constitute a major impediment to poverty alleviation, and inevitably lead to environmental degradation. Conditions are worse for conflict/disaster hit areas where a large human population is suddenly gathered, such as in refugee camps. Various technologies for sanitation, which may be suitable for post-disaster or post-conflict phases, have been developed. This study analyses the technological, environmental and economical suitability of the BIOSAN technology, in the post-disaster reconstruction. The BIOSAN technology is a hybrid of the ventilated improved pit-latrine (VIP) and sewerage technologies, and integrates the advantages of the two technologies while minimizing their shortcomings and enhancing the human quality of life. This study follows a BIOSAN technology model designed and constructed at the Kakamega Provincial General Hospital, in Western Kenya. The technology is very appropriate for institutional sanitation and is therefore, considered suitable for refugee camps in the intermediate emergency phase of a disaster or conflict event. Apart from providing an environmentally friendly sanitation, the technology also aims to harvest methane to be used as source of energy.
Keywords: BIOSAN latrine; Energy; Environment; Refugee camps